Informação, cultura e homeopatia: redes sociais e cuidado em saúde na comunidade do Morro dos Cabritos RJ - Campos, Gilda Zamith Ribeiro (2012)
Systematization of a homeopathic intervention addressed to children living in the Morro dos Cabritos, Rio de Janeiro, and undertaken by the Non Governmental Organization Homeopatia Ação Pelo Semelhante (NGO-HAPS). The study deals with an unprecedented aspect, as it extends its focus on the family of children accompanied by the homeopathy; it aims at understanding how information circulates within the families and social networks concerning children s health care, in order to perceive the knowledge development process in this context. The research general purpose is studying the social intervention potential of homeopathic medical rationality , as an informational practice, in the processes of values re-signification, autonomy strengthening, and improvement in families quality of life, in a community under social-economic vulnerability. Different methodological procedures have been adopted: data analysis from IBGE (Census-2000); survey of studies on the population of Morro dos Cabritos; documentary analysis at the NGO-HAPS; and interviews analysis through qualitative research. Among those responsible for children ( responsibles ), fourteen were interviewed (11 women who participated in two focal groups, and three who were individually interviewed). These participants accompanied their children s homeopathic treatment for a period of at least two years. A third focal group involved seven homeopaths from the NGO-HAPS, who participated in the project for a minimum period of three years. Interviews were based on semi-structured questions with different contents for the responsibles and the doctors. Among the results, it may be highlighted: overcoming of family preconceptions concerning homeopathy; broadening of health, illness, treatment and cure concepts; reduction of segregation regarding the connubial roles in children s care; empowerment of those responsible for children, which favors prevention and health promotion; improvement in families quality of life in different domains (physical and psychological aspects, independence level, social relations, environmental conditions, and personal beliefs); valorization of the responsibles as participants in child s care; increase of critical consciousness; and strengthening of their own identity ( responsibles and professionals). In conclusion, the homeopathic intervention in this community has been quite effective, as it respects population s cultural vision, welcomes individuals as subjects, not as objects, adopts an integral health vision, in addition to being able to solve most frequent health problems in this group. Achieving health constitutes a process for reaching cultural emancipation of subjects/ responsibles , as they understand that the dominant values of contemporary society act as barriers to health care. Timely, health information, inserted in a vision of integral care, seems to foster internalization/awareness of social reality, knowledge development, and responsibles empowerment oriented to children s care.